Evaluation of preoperative calculation methods of osteotomy size in ankylosing spondylitis with thoracolumbar or lumbar kyphosis - Cheng, Jie; Zhang, Shuwen; Sheng, Weibin (BMC musculoskeletal disorders, 2022)
To evaluate the accuracy of different preoperative calculation methods of osteotomy size in ankylosing spondylitis with thoracolumbar or lumbar kyphosis and analyze its clinical significance. Twenty-two cases of AS patients with thoracolumbar or lumbar kyphosis, from January 2015 to December 2018, who underwent one-level SPO surgery in our hospital, were retrospectively reviewed. The sagittal parameters were measured at pre-operation and last follow up using Surgimap software, and theoretical values of sagittal parameters were calculated according to pre-operative PI. The osteotomy angles of different methods were measured using Surgimap software. Paired t test was used to for the statistical analysis. The mean follow-up time of all patients was 30.00 [Formula: see text] 3.56 months. The osteotomy sites were located at T12 in 3 cases, L1 in 6 cases, L2 in 9 cases, and L3 in 4 cases. Compared to pre-operative sagittal parameters, post-operative PT, SS, LL, and SVA were significantly improved (P [Formula: see text] 0.05). Compared to the OVA (46.57 [Formula: see text] 2.32 [Formula: see text]), there was a significantly larger angle predicted by Surgimap method (53.80 [Formula: see text] 9.79 [Formula: see text]), CAM-HA method (56.61 [Formula: see text] 8.58 [Formula: see text]), and HP-HA method (60.07 [Formula: see text] 13.58 [Formula: see text]), respectively (P [Formula: see text] 0.05). But no significant difference was found between the postoperative osteotomy angle and those of SFA method (51.24 [Formula: see text] 12.14 [Formula: see text]) and FBI method (48.08 [Formula: see text] 12.49 [Formula: see text]) (P [Formula: see text] 0.05). For AS patients with thoracolumbar or lumbar kyphosis, the SFA method, FBI method, and Surgimap method can be used to predict the osteotomy angle precisely, however, considering the rationality of parameter settings and the operability, SFA method is relatively more suitable for such population.